Laparoscopic vs. open distal gastrectomy for locally advanced gastric cancer: A systematic review and meta-analysis of randomized controlled trials - Yan, Yong; Ou, Caiwen; Cao, Shunwang; Hua, Yinggang; Sha, Yanhua (Frontiers in Surgery, 2023)
Objective The aim of this systematic review and meta-analysis is to compare the short- and long-term outcomes of laparoscopic distal gastrectomy (LDG) with those of open distal gastrectomy (ODG) for patients with advanced gastric cancer (AGC) who exclusively underwent distal gastrectomy and D2 lymphadenectomy in randomized controlled trials (RCTs). Background Data in published meta-analyses that included different gastrectomy types and mixed tumor stages prevented an accurate comparison between LDG and ODG. Recently, several RCTs that compared LDG with ODG included AGC patients specifically for distal gastrectomy, with D2 lymphadenectomy being reported and updated with the long-term outcomes. Methods PubMed, Embase, and Cochrane databases were searched to identify RCTs for comparing LDG with ODG for advanced distal gastric cancer. Short-term surgical outcomes and mortality, morbidity, and long-term survival were compared. The Cochrane tool and GRADE approach were used for evaluating the quality of evidence (Prospero registration ID: CRD42022301155). Results Five RCTs consisting of a total of 2,746 patients were included. Meta-analyses showed no significant differences in terms of intraoperative complications, overall morbidity, severe postoperative complications, R0 resection, D2 lymphadenectomy, recurrence, 3-year disease-free survival, intraoperative blood transfusion, time to first liquid diet, time to first ambulation, distal margin, reoperation, mortality, or readmission between LDG and ODG. Operative times were significantly longer for LDG [weighted mean difference (WMD) 49.2 min, p < 0.05], whereas harvested lymph nodes, intraoperative blood loss, postoperative hospital stay, time to first flatus, and proximal margin were lower for LDG (WMD −1.3, p < 0.05; WMD −33.6 mL, p < 0.05; WMD −0.7 day, p < 0.05; WMD −0.2 day, p < 0.05; WMD −0.4 mm, p < 0.05). Intra-abdominal fluid collection and bleeding were found to be less after LDG. Certainty of evidence ranged from moderate to very low. Conclusions Data from five RCTs suggest that LDG with D2 lymphadenectomy for AGC has similar short-term surgical outcomes and long-term survival to ODG when performed by experienced surgeons in hospitals contending with high patient volumes. It can be concluded that RCTs should highlight the potential advantages of LDG for AGC. Systematic Review Registration PROSPERO, registration number CRD42022301155.